Combined Treatment for Recurrent Herpetic Stromal Keratitis with Ulceration: a Case Report - L.F. Troychenko; T.B. Gaydamaka; G.I. Drozhzhyna (Journal of Ophthalmology, 2019)
Herpes simplex keratitis (HSK) is a severe ophthalmic pathology which comprises 20-50% of inflammatory diseases in the cornea. Since keratitis is characterized by a long-term duration, severity, and a tendency to recurrence, studies on ophthalmic herpes and searches for new treatments are of great relevance.